Dynamic Memory Regeneration - Aarabi, Pegah; Aarabi, Parham (Conference proceedings - IEEE International Conference on Systems, Man, and Cybernetics, 2020)
In this paper, we examine a practical implementation of dynamic memory regeneration for the purpose of treating memory loss. Inspired by the refresh cycles in computer Dynamic Random Access Memory (DRAM) circuits, we propose a condensed audiovisual summary that refreshes a subject's memory within a specific amount of time. We explore the impact of the audiovisual refresh cycle time on the overall probability of memory loss, and examine how this refresh time is related to parameters such as refresh cycle duration, and the intrinsic memory loss time. Based on several simplifying assumptions, we propose a model for an ideal memory refresh duration that would minimize the probability of memory loss.